Tools/instruments for assessing YouTube videos on surgical procedures for patient/consumer health education: a systematic review - Pavuloori, Manasa; Lin, Amy; Mi, Misa (Frontiers in Public Health, 2025)
BackgroundYouTube is becoming an increasingly popular platform for health education; however, its reliability for surgical patient education remains largely unexplored. Given the global prevalence of preoperative anxiety, it becomes essential to ensure accurate information online.ObjectivesThe objective is to assess tools/instruments used to evaluate YouTube videos on surgical procedures created to educate patients or health consumers.MethodsIn June 2023, a comprehensive literature search was conducted on PubMed, PsycINFO, CINAHL, and Scopus. Primary studies with empirical data that evaluate English YouTube videos to educate patients about surgical procedures in all specialties were included. Two reviewers independently completed title/abstract and full text screening, and data extraction in duplicate. The data extracted includes the number of videos evaluated, assessment tools, outcomes of significance, specific objectives, and features examined.ResultsA total of 41 studies were included in the review. The most commonly used evaluation tools were DISCERN (21 studies), the Global Quality Scale (11 studies), and the JAMA benchmark criteria (11 studies). Notably, 23 studies used a unique assessment instrument, and several studies employed more than one tool concurrently. Of the total studies included, 88% of the articles determined that patients were not adequately educated by YouTube videos per the ratings of the assessment tools, and 19 out of 41 articles mentioned that videos from professional sources were most useful.ConclusionsThis systematic review suggests that the educational qualities in YouTube videos are substandard. Patients should be cautious when relying solely on YouTube videos for medical guidance. Surgeons and medical institutions are encouraged to direct patients to high-quality patient education sources and create accessible medical content. As there is variability in the quality assessment tools used for evaluation, a standardized approach to creating and assessing online medical videos would improve patient education.